Implementasi Literasi Digital Pada Pembelajaran Maharah Qira’ah Al-Mutawassithah - Rima Ajeng Rahmawati (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2023)
There are some problems in learning Maharatul Qira'ah that is still focused on learning modules, this has resulted in some students experiencing difficulties in reading Arabic texts especially in education theme because many contemporary terms that are rarely used and are encountered in everyday life. Researchers used a qualitative approach with a descriptive-analytical method. The purpose of researchers using a qualitative approach in this study is to examine and find out how digital literacy is implemented in learning Maharatul Qira'ah al-Mutawassithah. Data collection techniques used are interviews, observation and documentation. Triangulation was carried out to check the validity of the data in this study by data source triangulation or informant triangulation. The results of this study stated that the implementation of digital literacy in learning Maharatul Qira'ah in students of the Intensive Class Arabic Education Study Program STIT Darul Fattah Bandar Lampung uses several platforms and applications that can be accessed via gadgets or PCs. The media to access digital literacy include: whatsapp, google meet, google scholar and google form. With the use of computer and internet-based learning media can achieve learning targets and increase student motivation. In addition, the use of gadgets is very helpful for students to finding learning resources from the internet easily, economically and unlimitedly with Brainly, Wikipedia and Google Scholar. Keywords: Implementation, Digital Literacy, Maharatul Qira'ah